Pengembangan Aplikasi Web Pengelolaan Data pada Proses Uji Beton Ready Mix PT. Adhi Persada Beton menggunakan Metode Extreme Programming - Alfin Rizqiansi Ansory; Diah Priharsari; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PT. Adhi Persada Beton is a company that produces precast and ready mix concrete. This concrete production aims to meet the needs of precast concrete on projects handled by PT. Adi Karya. In the concrete testing process that was carried out there were several problems such as the slipping of test documents and the lack of efficiency in testing time. Nowadays, the development of technology is growing rapidly, which is companies need new innovations to improve their business process.Therefore, a solving the problem the researcher develop a web-based application.This web- based application has a function for recording test data carried out at the Adhi Persada Beton Factory. This system can help manufacturers to reduce paper usage, minimize data loss and save costs and digital storage so that test data can be easily tracked in the future for reuse. In this development using the Extreme Programming method with Codeigniter framework and MySQL as the database. This system testing using Black Box to test functionally system. The test result on this system indicate that all the functionalities contained in the system are declared valid.